Musical genius and/or nasty piece of work? Dealing with violence and sexual assault in accounts of popular music’s past - Strong, Catherine; Rush, Emma (Continuum, 2018)
For many years, the mistreatment of women in particular has essentially been normalized in many parts of the music industry. In recent years, however, there has been an increase in women coming forward and telling their stories, and asking that men be held accountable for wrongdoing. This interdisciplinary (sociology and philosophy) paper pursues two key feminist questions prompted by recent developments. Firstly: How has the construction of the history of popular music legitimated the continuation of this situation? ‘Looking back’ historically and sociologically, examples are provided of the legitimation or ignoring of violence against women (VAW) in the history of popular music to date. Secondly: How should we [archivists, historians, heritage curators and popular music educators], from now on, construct the history of popular music in a way that doesn’t legitimate VAW? Turning to ‘look forward’, applied ethics frameworks are used to explore different aspects of this second question.
Keywords: Bibliographie; Nettoyer